Lithium battery fast charging electrolyte
Patent Information
- Application Number
- CN202611274297.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]然而,上述现有电解液体系在45℃长期存储叠加每月大电流放电的复合工况下仍存在显著技术缺陷:45℃长期存储时,酯类溶剂易发生缓慢分解,与电极界面持续发生副反应,产生微量气体导致电芯胀气,同时LiPF6锂盐水解生成HF,持续腐蚀正负极界面,破坏电极结构与界面膜完整性;存储过程中每月的大电流放电,会因电解液离子电导率随存储时间下降、界面膜离子传输阻力增大,导致浓差极化加剧、放电平台骤降、容量输出不足,最终致使电芯经45℃长期存储后容量保持率低、放电性能衰减严重,无法满足实际应用的存储与使用需求
1、优异的氟-腈相容特性:修饰型氟代烃通过氰基侧链实现与支链化腈类的分子级相容,电解液在-40℃~80℃范围内无相分离,25℃下粘度低至3.5~4.2 mPa•s,介电常数≥65 F/m,兼顾低粘度与高介电常数,为高离子电导率奠定基础。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, and specifically relates to a fast-charging electrolyte for lithium batteries. Background Technology
[0002] Lithium iron phosphate (LFP) graphite cells have become the core choice for power batteries, energy storage power supplies, start-stop power supplies, and data center power supplies due to their low cost, superior safety, and long cycle life. In practical applications such as data center power supplies, cells often face long-term storage conditions at 45°C, and require periodic high-current discharges of 10C-50C every month during storage. This places stringent demands on both the storage stability of the electrolyte and its adaptability to high-rate discharge.
[0003] In existing technologies, to address the issues of fast charging and high voltage in lithium-ion batteries, fluoronitriles have been used as solvents in lithium-ion battery electrolytes. These electrolytes combine the wide electrochemical window and ultra-high ionic conductivity of nitrile electrolytes with the excellent film-forming properties and low interfacial impedance of fluoride electrolytes. Studies have also explored the use of nitrile organic solvents in combination with fluorinated diluents to prepare fast-charging electrolytes, leveraging the high dielectric constant of nitriles to dissolve lithium salts and improve reduction stability. Furthermore, regarding additives, there are reports of compounding fluoroethylene carbonate with nitrile compounds to improve battery performance.
[0004] However, the existing electrolyte system still has significant technical defects under the combined conditions of long-term storage at 45°C and monthly high-current discharge: During long-term storage at 45°C, ester solvents are prone to slow decomposition, which continuously reacts with the electrode interface, producing trace amounts of gas that cause cell swelling. At the same time, LiPF6 lithium salt hydrolyzes to generate HF, which continuously corrodes the positive and negative electrode interfaces, damaging the electrode structure and the integrity of the interface film. During the storage process, the monthly high-current discharge will cause concentration polarization to intensify, the discharge plateau to drop sharply, and the capacity output to be insufficient due to the decrease in electrolyte ionic conductivity with storage time and the increase in ion transport resistance of the interface film. Ultimately, this results in low capacity retention and severe discharge performance degradation of the cell after long-term storage at 45°C, which cannot meet the storage and use requirements of practical applications.
[0005] Therefore, developing an electrolyte suitable for long-term storage at 45°C in lithium iron phosphate-graphite cells and compatible with irregular monthly discharge at high currents of 10C-50C has become a pressing technical challenge in this field. Summary of the Invention
[0006] This invention addresses the technical shortcomings of existing lithium iron phosphate-graphite battery electrolytes, such as solvent decomposition, lithium salt hydrolysis, interface degradation, and increased concentration polarization, under long-term storage at 45°C and high-rate discharge conditions. It provides a fluorocarbon-nitrile synergistic fast-charging electrolyte for lithium batteries, aiming to achieve a dual breakthrough in stability during long-term storage at 45°C and high-rate charge / discharge performance above 10C. Simultaneously, it improves the electrolyte's chemical stability, hydrolysis resistance, and electrode interface protection capabilities, thereby enhancing capacity retention and high-rate cycle life.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A fast-charging electrolyte for lithium batteries is suitable for long-term storage at 45°C in lithium iron phosphate-graphite cells and is compatible with irregular 10C-50C high-current discharge every month. The electrolyte is composed of four parts: a fluorinated hydrocarbon-nitrile graded compatible organic solvent, a fluorinated-nitrile synergistic compounded lithium salt, a fluorinated-nitrile interface regulating composite additive, and a multifunctional synergistic agent. The mass percentage of the four parts is 55-75:15-30:6-18:2-8.
[0008] Furthermore, the mass percentage of the fluorinated hydrocarbon-nitrile graded compatible organic solvent is 55-75%, and it is compounded from modified fluorinated hydrocarbons, branched nitriles and low viscosity carbonate diluent in a mass ratio of 30-45:20-35:25-40. The modified fluorocarbon is selected from one or two of fluoroethyl carbonates and fluoromethyl propyl ethers containing cyano side chains. The branched nitrile is selected from one or two of isoprene, methylmalononitrile, and tert-butylacetonitrile; The low-viscosity carbonate diluent is a mixture of dimethyl carbonate and diethyl carbonate in a 1:1 mass ratio.
[0009] Furthermore, the mass percentage of the fluorine-nitrile synergistic compounded lithium salt is 15-30%, and it is compounded from lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate (LiDFOB), and nitrile complexed lithium salt (LiN(SO2CF3)(SO2CN)) in a mass ratio of 5-7:2-4:1-3.
[0010] Furthermore, the fluorine-nitrile interface regulating composite additive has a mass ratio of 6-18% and includes the following components: Fluorine-nitrile synergistic film-forming agent: It is a compound of fluoroethylene carbonate and cyanopropylene in a mass ratio of 1:2, and the total addition amount is 2-6% of the total mass of the electrolyte; Positive electrode nitrile passivating agent: selected from trifluoromethylphenyl isocyanate or pentafluorophenyl isocyanate, with an addition amount of 1-3% of the total mass of the electrolyte; Interfacial bonding enhancer: fluoroacrylate oligomer, added at a rate of 0.5-2% of the total mass of the electrolyte.
[0011] Furthermore, the multifunctional synergistic agent comprises 2-8% by mass and includes the following components: Dual-effect hydrolysis inhibitor: composed of tris(trimethylsilyl)borate ester and fluorosilane coupling agent in a 1:1 mass ratio, with a total addition amount of 0.5-2% of the total mass of the electrolyte; Free radical scavenger: selected from triphenyl thiophosphate or dithiophosphate, added at a rate of 0.5-2% of the total mass of the electrolyte; High-rate ion transporter: boron-fluorine complex (LiBF2(C2O4)), the amount added is 1-4% of the total mass of the electrolyte.
[0012] Furthermore, the electrolyte is prepared by dissolving a fluorine-nitrile synergistic lithium salt in a fluorinated hydrocarbon-nitrile graded compatible organic solvent under inert gas protection, then adding a fluorine-nitrile interface regulating composite additive and a multifunctional synergistic agent, and stirring at room temperature until completely dissolved to obtain the electrolyte.
[0013] Compared with the prior art, the beneficial effects of the present invention are: 1. Excellent fluorine-nitrile compatibility: Modified fluorinated hydrocarbons achieve molecular-level compatibility with branched nitriles through cyano side chains. The electrolyte exhibits no phase separation within the range of -40℃ to 80℃, with a viscosity as low as 3.5~4.2 mPa•s at 25℃ and a dielectric constant ≥65 F / m. This balance of low viscosity and high dielectric constant lays the foundation for high ionic conductivity.
[0014] 2. Superior long-term storage stability at 45℃: The high stability of fluorinated hydrocarbons and the low reactivity of branched nitrile compounds, combined with the synergistic effect of hydrolysis inhibitors and free radical scavengers, effectively suppress solvent decomposition, lithium salt hydrolysis, and nitrile side reactions. After 60 months of storage at 45℃ and one 50C discharge per month, the HF content in the electrolyte of the lithium iron phosphate-graphite cell is ≤40ppm, far superior to existing single fluorinated hydrocarbon or nitrile electrolytes.
[0015] 3. Excellent high-rate charge and discharge performance: The high dielectric constant of nitriles and the high dissociation degree of compound lithium salts, combined with the synergistic effect of high-rate ion transport agents, result in an electrolyte room temperature ionic conductivity ≥12 mS / cm, supporting 12C fast charging / 20C discharging, 12C constant current charging ratio ≥90%, and 20C discharge capacity retention ≥92%, effectively solving the high-rate polarization problem of fluorinated hydrocarbon electrolytes.
[0016] 4. Excellent fluorine-nitrile synergistic interface protection: A fluorine-nitrile cross-linked SEI / CEI double film is formed on the positive and negative electrode surfaces, improving density by more than 50% and ion conductivity ≥1×10 -6 S / cm effectively resists interface degradation at 45℃ storage and lithium intercalation impact at high rates, avoiding active lithium loss and electrode corrosion.
[0017] 5. Long-term cycle stability under all operating conditions: The four components work synergistically to achieve a capacity retention rate of ≥80% after 60 months of storage at 45℃, a capacity retention rate of ≥75% after 1000 cycles of 10C charge / 20C discharge, and a capacity retention rate of ≥70% after 500 cycles of 5C charge / 10C discharge at 60℃. Detailed Implementation
[0018] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below.
[0019] Example 1: Composition and preparation of electrolyte 1: 51.0 g of fluorinated hydrocarbon-nitrile graded compatible organic solvent (containing 18 g of cyano side-chain fluoroethyl carbonate, 12 g of isoprene, and 21 g of a mixture of dimethyl carbonate and diethyl carbonate in a 1:1 ratio). 26.0g of fluorine-nitrile synergistic compound lithium salt (LiPF6 17.0g, LiDFOB 6.0g, LiN(SO2CF)) 33 (SO2CN)3.0g); 16.0g of fluorinated-nitrile interface regulating composite additive (4.0g of fluoroethylene carbonate, 8.0g of cyanopropionic acid vinyl ester, 3.0g of trifluoromethylphenyl isocyanate, and 1.0g of fluoroacrylate oligomer). Multifunctional synergist 7.0g (tris(trimethylsilyl)boronic acid ester 1.0g, fluorosilane coupling agent 1.0g, triphenyl thiophosphate 1.5g, LiBF2(C2O4) 3.5g).
[0020] In an argon-filled glove box, the above-mentioned fluorine-nitrile synergistic lithium salt was dissolved in a fluorinated hydrocarbon-nitrile graded compatible organic solvent, and then a fluorine-nitrile interface regulating composite additive and a multifunctional synergistic agent were added. The mixture was stirred at room temperature for 2 hours until completely dissolved to obtain electrolyte 1.
[0021] Example 2: Composition and preparation of electrolyte 2: 58.5g of a fluorinated hydrocarbon-nitrile graded compatible organic solvent (20g of fluorinated methyl propyl ether, 15g of methyl malononitrile, and 23.5g of a mixture of dimethyl carbonate and diethyl carbonate in a 1:1 ratio); 25.0g of fluorine-nitrile synergistic compound lithium salt (LiPF6 19.0g, LiDFOB 4.0g, LiN(SO2CF3)(SO2CN) 2.0g); 11.8g of fluorinated-nitrile interface regulating composite additive (3.0g of fluoroethylene carbonate, 6.0g of cyanopropionic acid vinyl ester, 2.0g of trifluoromethylphenyl isocyanate, and 0.8g of fluoroacrylate oligomer). Multifunctional synergist 5.4g (tris(trimethylsilyl)boronic acid ester 0.7g, fluorosilane coupling agent 0.7g, triphenyl thiophosphate 1.2g, LiBF2(C2O4) 2.8g).
[0022] Electrolyte 2 was prepared according to the preparation method of Example 1.
[0023] Example 3: Composition and preparation of electrolyte 3: 51.3 g of a fluorinated hydrocarbon-nitrile graded compatible organic solvent (containing 16 g of cyano side-chain fluoropropyl carbonate, 10 g of tert-butylacetonitrile, and 25.3 g of a mixture of dimethyl carbonate and diethyl carbonate in a 1:1 ratio). 22.5g of fluorine-nitrile synergistic compound lithium salt (LiPF6 15.0g, LiDFOB 5.0g, LiN(SO2CF3)(SO2CN) 2.5g); 11.2g of fluorinated-nitrile interface regulating composite additive (2.5g of fluoroethylene carbonate, 5.0g of cyanopropionic acid vinyl ester, 2.5g of pentafluorophenyl isocyanate, and 1.2g of fluoroacrylate oligomer). Multifunctional synergist 6.0g (tris(trimethylsilyl)boronic acid ester 0.9g, fluorosilane coupling agent 0.9g, dithiophosphate ester 1.0g, LiBF2(C2O4) 3.2g).
[0024] Electrolyte 3 was prepared according to the preparation method of Example 1.
[0025] Comparative Example 1 (Single Fluorinated Hydrocarbon Electrolyte): Electrolyte 4 consists of: 25.0 g LiPF6, 5.0 g LiDFOB, 5.0 g fluoroethylene carbonate, and 2.0 g tris(trimethylsilyl)borate, dissolved in 63.0 g of a fluorocarbon + carbonate solvent (25 g fluoroethyl carbonate, 38 g dimethyl carbonate and methyl ethyl carbonate), free of nitrile components and interface modifiers. Electrolyte 4 was prepared according to the method described in Example 1.
[0026] Comparative Example 2 (Single Nitrile Electrolyte): Electrolyte 5 consists of: 25.0 g LiPF6, 3.0 g LiFSI, 3.0 g vinyl cyanopropionate, and 2.0 g triphenyl thiophosphate, dissolved in 67.0 g of a nitrile + carbonate solvent (20 g malononitrile, 47 g of a 1:1 mixture of dimethyl carbonate and diethyl carbonate), free of fluorinated hydrocarbon components and fluorinated film-forming agents. Electrolyte 5 was prepared according to the preparation method of Example 1.
[0027] Test Example: Full-condition performance test The electrolytes prepared in Examples 1-3 and Comparative Examples 1-2 were injected into 40135-10Ah lithium iron phosphate-graphite cells to prepare test batteries. These batteries underwent long-term storage at 45℃ and periodic high-rate charge-discharge full-condition testing. The test items and methods are as follows: Long-term storage at 45℃: Store at 45℃ for 60 months, discharge at 50C once a month and then continue to store at full charge. Test the HF content, capacity retention rate and 50C discharge capacity retention rate after 60 months of storage. High-rate charge and discharge: Testing 12C fast charging constant current ratio and 20C discharge capacity retention rate; Cyclic stability: Capacity retention was tested after 1000 cycles of 10C charge / 20C discharge at 25℃.
[0028] The test results are shown in the table below:
[0029] As shown in Table 1, the fluorinated hydrocarbon-nitrile synergistic electrolytes of Examples 1-3 are significantly superior to the single fluorinated hydrocarbon electrolyte (Comparative Example 1) and the single nitrile electrolyte (Comparative Example 2) in terms of storage stability at 45℃, high-rate charge-discharge performance, and cycle stability. Among them, Example 1 has the best performance, with an HF content of only 32ppm after 60 months of storage at 45℃, a capacity retention rate of 92.6%, a 12C fast charge constant current ratio of 93.4%, a 50C discharge capacity retention rate of 94.3%, and a capacity retention rate of 78.1% after 1000 cycles at 10C / 20C.
[0030] The above results demonstrate that this invention, through the synergistic effect of a fluorine-nitrile graded compatible solvent system, a compound lithium salt system, an interface-regulating additive system, and a multifunctional auxiliary agent system, successfully achieves a deep integration of the advantages of fluorinated hydrocarbons and nitriles, solves the core defects of existing technologies, and can perfectly adapt to the combined operating conditions of lithium iron phosphate-graphite cells under the combined conditions of long-term storage at 45°C and monthly high-current discharge.
[0031] Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this invention without departing from the spirit and scope of the technical solutions of this invention, and all such modifications or substitutions should be covered within the scope of the claims of this invention.
Claims
1. A fast-charging electrolyte for lithium batteries, characterized in that, The electrolyte comprises a fluorinated hydrocarbon-nitrile graded compatible organic solvent, a fluorinated-nitrile synergistic compounded lithium salt, a fluorinated-nitrile interface regulating composite additive, and a multifunctional synergistic agent, with a mass percentage of 55-75:15-30:6-18:2-8.
2. The lithium battery fast-charging electrolyte according to claim 1, characterized in that, The mass percentage of the fluorinated hydrocarbon-nitrile graded compatible organic solvent is 55-75%, and it is compounded by modified fluorinated hydrocarbons, branched nitriles and low viscosity carbonate diluent in a mass ratio of 30-45:20-35:25-40. The modified fluorocarbon is selected from one or two of fluoroethyl carbonates and fluoromethyl propyl ethers containing cyano side chains. The branched nitrile is selected from one or two of isoprene, methylmalononitrile, and tert-butylacetonitrile; The low-viscosity carbonate diluent is a mixture of dimethyl carbonate and diethyl carbonate in a 1:1 mass ratio.
3. The lithium battery fast-charging electrolyte according to claim 1, characterized in that, The fluorine-nitrile synergistic compound lithium salt has a mass ratio of 15-30% and is composed of lithium hexafluorophosphate, lithium difluorooxalate borate and nitrile complex lithium salt LiN(SO2CF3)(SO2CN) in a mass ratio of 5-7:2-4:1-3.
4. The lithium battery fast-charging electrolyte according to claim 1, characterized in that, The fluorine-nitrile interface regulating composite additive has a mass ratio of 6-18% and includes the following components: Fluorine-nitrile synergistic film-forming agent: It is composed of fluoroethylene carbonate and cyanopropylene vinyl ester in a mass ratio of 1:2, and the total addition amount is 2-6% of the total mass of the electrolyte; Positive electrode nitrile passivating agent: selected from trifluoromethylphenyl isocyanate or pentafluorophenyl isocyanate, with an addition amount of 1-3% of the total mass of the electrolyte; Interfacial bonding enhancer: fluoroacrylate oligomer, added at a rate of 0.5-2% of the total mass of the electrolyte.
5. The lithium battery fast-charging electrolyte according to claim 1, characterized in that, The multifunctional synergistic agent comprises 2-8% by mass and includes the following components: Dual-effect hydrolysis inhibitor: composed of tris(trimethylsilyl)borate ester and fluorosilane coupling agent in a 1:1 mass ratio, with a total addition amount of 0.5-2% of the total mass of the electrolyte; Free radical scavenger: selected from triphenyl thiophosphate or dithiophosphate, added at a rate of 0.5-2% of the total mass of the electrolyte; High-rate ion transporter: LiBF2(C2O4), added at 1-4% of the total mass of the electrolyte.
6. The lithium battery fast-charging electrolyte according to any one of claims 1-5, characterized in that, The electrolyte is suitable for lithium iron phosphate-graphite cells.
7. The lithium battery fast-charging electrolyte according to any one of claims 1-5, characterized in that, The electrolyte is prepared as follows: under inert gas protection, a fluorine-nitrile synergistic compounded lithium salt is dissolved in a fluorinated hydrocarbon-nitrile hierarchically compatible organic solvent, and then a fluorine-nitrile interface regulating composite additive and a multifunctional synergistic agent are added. The solution is stirred at room temperature until completely dissolved to obtain the electrolyte.
8. A lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The electrolyte is the lithium battery fast-charging electrolyte according to any one of claims 1-5.
9. The lithium-ion battery according to claim 8, characterized in that, The positive electrode is a lithium iron phosphate positive electrode, and the negative electrode is a graphite negative electrode.
10. The application of the lithium battery fast-charging electrolyte according to any one of claims 1-5 in the preparation of lithium iron phosphate-graphite cells, wherein the cells are used for long-term storage at 45°C and are compatible with monthly irregular high-current discharge of 10C-50C.